Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae) - Kondorosy, Előd; Ishikawa, Tadashi; Rédei, Dávid (Zootaxa, 2016)
The identity of Metochus abbreviatus Scott, 1874 (Hemiptera: Heteroptera: Rhyparochromidae: Rhyparochrominae: Rhyparochromini) is clarified based on reexamination of the lectotype. The subjective synonymy of Dieuches kreyenbergi Breddin, 1906 with M. abbreviatus is confirmed. The following new subjective synonymies are proposed: Rhyparochromus erosus Walker, 1872 = Metochus abbreviatus Scott, 1874, syn. nov. = Metochus holsti Distant, 1918, syn. nov. Bibliographies of the names are provided and it is demonstrated that the name M. abbreviatus is in prevailing usage. Reversion to the senior name Rh. erosus is considered to be undesirable, therefore an application has simultaneously been submitted to the International Commission on Zoological Nomenclature to give the specific name abbreviatus precedence over the specific name erosus. The diagnostic characters, bionomics and distribution of the species are briefly reviewed.